Effect of allergen-specific immunotherapy on CD4+ T cells. Issue 6 (December 2015) - Unknown
Abstract : Purpose of review: The aims of this review are to discuss the impact of chronic high-dose allergen exposure on allergen-specific CD4( + ) T-cell subset during allergen-specific immunotherapy (AIT) and discuss recent advances supporting novel mechanisms for desensitization and tolerance induction during AIT. Recent findings: New technologies for direct molecular and cellular analysis have now provided an unprecedented opportunity to compare the functions and phenotypes of allergen-specific T cells at a single cell level, both in the context of disease and clinical intervention. Recent studies have demonstrated that AIT may restore tolerance by transiently inducing interleukin (IL)-10 producing T cells followed by selective deletion of allergen-specific TH 2 cell subset. Summary: With antigen-specific TH2 cells at the core of the allergic process in atopic individuals, the duration and dose of antigen exposure can be the driving force behind current AIT protocol. Mechanisms modulating allergen-specific CD4( + ) T-cell responses may include autocrine IL-10 production to limit excessive TH2 cell effector responses, T-cell exhaustion, and preferential proallergic TH2 cell deletion allowing concurrent downregulating T-cell responses to emerge. Administration of AIT in the context of immune modulating strategies able to induce counter-regulatory immune response may lead to improved AIT with durable clinical benefit.